Uterus Hyperplasia and Increased Carcinogen-Induced Tumorigenesis in Mice Carrying a Targeted Mutation of the Chk2 Phosphorylation Site in Brca1 - Kim, Sang Soo (American Society for Microbiology, 2004)
The tumor suppressor BRCA1 contains multiple functional domains that interact with many proteins. After DNA damage, BRCA1 is phosphorylated by CHK2 at serine 988, followed by a change in its intracellular location. To study the functions of CHK2-dependent phosphorylation of BRCA1, we generated a mouse model carrying the mutation S971A (S971 in mouse Brca1 corresponds to S988 in human BRCA1) by gene targeting. Brca1(S971A/S971A) mice were born at the expected ratio without a developmental defect, unlike previously reported Brca1 mutant mice. However, Brca1(S971A/S971A) mice suffered a moderately increased risk of spontaneous tumor formation, with a majority of females developing uterus hyperplasia and ovarian abnormalities by 2 years of age. After treatment with DNA-damaging agents, Brca1(S971A/S971A) mice exhibited several abnormalities, including increased body weight, abnormal hair growth pattern, lymphoma, mammary tumors, and endometrial tumors. In addition, the onset of tumor formation became accelerated, and 80% of the mutant mice had developed tumors by 1 year of age. We demonstrated that the Brca1(S971A/S971A) cells displayed reduced ability to activate the G(2)/M cell cycle checkpoint upon γ-irradiation and to stabilize p53 following N-methyl-N′-nitro-N-nitrosoguanidine treatment. These observations suggest that Chk2 phosphorylation of S971 is involved in Brca1 function in modulating the DNA damage response and repressing tumor formation.